KELEMBAGAAN LAHAN DAN TENAGA KERJA PADA USAHATANI TANAMAN PANGAN DI KABUPATEN GUNUNGKIDUL - Suwarto Suwarto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2005)
This research aims to find out the effect of land and labour institution on land productivity, cost of production, and farm income.The research was conducted at Candisari, Hargosari Village, Kecamatan Tanjungsari, and at Widoro, Balong Village, Kecamatan Giri Subo, Gunung Kidul. The primary data was taken during Septembe to December 2004.The result of this research found that the household labour, head of household education and age, the use of nitrogen and phosphat fertilizer increases the land productivity. On the contrary , farmer’s asset value and size of farm decrease land productivity. The self-owned land productivity is higher than the rented one belonging to Hamengku Buwono (HB), land productivity of forestation department lan is lower than the rented one belonging to HB.Land productivity, age and education of the household head, and the use of input (nitrogen, phosphate, and organic fertilizer, and seed) increase the production cost of food crop farming. Similarly, the uses of tenaga kerja upahan, royongan, and Rtan or arisan increase the production cost of food crop farming. The farm production cost in Lungguh-Kas Desa-milik Perseorangan (LKP) rented land is greater than the one in HB-rented land.The size of farm, the use of household labour, and education of household head increases the food crop farm income. On the contrary, the use of non household labour decrease the farm income. The food crop farm income of the workr-owner-farmer is higher than the one of farmer renting HB land. The income of farmer renting LKP land is lower than the one of the farmer renting the HB land, and farm income of the farmer easily accesing market is higher than that one who is relatively difficult to acces market.